2010
DOI: 10.1111/j.1365-3083.2010.02456.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunological Responses of Plague Vaccines F1 + rV270 and EV76 in Chinese-Origin Rhesus Macaque, Macaca mulatta

Abstract: The subunit vaccine SV1 (20 μg F1 + 10 μg rV270) has been identified as the optimal formulation in mice, which provided a good protection against plague in mice, guinea pigs and rabbits. To compare SV1 and SV2 (200 μg F1 + 100 μg rV270) with live attenuated vaccine EV76, antibody responses, protective efficacy, cytokines (IFN‐γ, TNF‐α, IL‐2, IL‐4, IL‐10 and IL‐12) production, CD4/CD8 ratio and CD69+ T‐cell activation marker were determined in sera of the immunized Chinese‐origin rhesus macaques, Macaca mulatta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Virulence of 10055 determined by oral administration in Swiss Webster mice demonstrated that the LD 50 of 10055 increased at least by 10 2 -fold (Ͼ4 ϫ 10 9 CFU) compared to that of the wild-type strain (LD 50 ϭ 5 ϫ 10 7 CFU). But we did not observe any changes in the virulence of 10052 (⌬msbB868) and 10053 [⌬msbB868::P msbB ::msbB (EC) ] (data not shown).…”
Section: Constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Virulence of 10055 determined by oral administration in Swiss Webster mice demonstrated that the LD 50 of 10055 increased at least by 10 2 -fold (Ͼ4 ϫ 10 9 CFU) compared to that of the wild-type strain (LD 50 ϭ 5 ϫ 10 7 CFU). But we did not observe any changes in the virulence of 10052 (⌬msbB868) and 10053 [⌬msbB868::P msbB ::msbB (EC) ] (data not shown).…”
Section: Constructionmentioning
confidence: 99%
“…Actual numbers of CFU inoculated were determined by plating serial dilutions onto LB agar. The experiment was repeated one time, and data were combined to calculate the LD 50 .…”
Section: Table 2 Primers Used In This Workmentioning
confidence: 99%
See 2 more Smart Citations
“…(25), which is considered avirulent in humans but highly lethal in mice (26). Strain 141 was isolated from Marmota himalayana in the Qinghai-Tibet plateau and is highly virulent to both humans and Rhesus macaques (27)(28)(29). Y. pestis bacilli were grown overnight at 26˚C with continuous shaking in Bacto heart infusion broth.…”
mentioning
confidence: 99%